Zolotai͡a kollekt͡sii͡a volshebnykh skazok : Bremenskie muzykanty ; Krasavit͡sa i Chudovishche ; Gulliver - Beli͡akova, A. A.; Leprince de Beaumont, Jeanne-Marie, 1711-1780; Swift, Jonathan, 1667-1745 (Mir knigi, 2007)
Three popular children's stories.